Pediatric Central Nervous System Tumors: State-of-the-Art and Debated Aspects - Foster, Mitchell T.; Harishchandra, Lalgudi Srinivasan; Mallucci, Conor (Frontiers in Pediatrics, 2018)
Abstract Paediatric neuro-oncology surgery continues to progress in sophistication, largely driven by advances in technology used to aid the following aspects of surgery: operative planning (advanced MRI techniques including fMRI and DTI), intraoperative navigation (preoperative MRI, ioMRI, and ioUS), tumour visualization (microscopy, endoscopy, fluorescence), tumour resection techniques (ultrasonic aspirator, micro-instruments, micro-endoscopic instruments), delineation of the resection extent (ioMRI, ioUS, and fluorescence), and intraoperative safety (neurophysiological monitoring, ioMRI). This article discusses the aforementioned technological advances, and their multimodal use to optimize safe paediatric neuro-oncology surgery.